PEMBINAAN JURNALISTIK SEBAGAI CITIZEN JOURNALIST DASAR PADA PAC GP ANSOR BATAM: PONDOK PESANTREN SIRRUL ILLAHIYAH: Journalistic Development as a Basic Citizen Journalist in PAC GP Ansor Batam: Islamic Boarding School Sirrul Illahiyah - Sholihul Abidin; Angel Purwanti; Timbul Dompak; Ilovia Nadine; Paramitha Khodijah; Rani Wardaniah (ASOSIASI IDEBAHASA KEPRI, 2023)
Citizen journalism was present in Indonesia beginning with the tsunami disaster in Aceh in 2004. Recorded images that could not be covered directly by journalists were finally able to be witnessed by wide audiences both locally, nationally, and internationally. So that the presence of citizen journalism using social media makes it a competitor as well as a complement in producing information for mass media institutions. GP Ansor (GP) is a youth, social, national, and religious organization with a populist character. This coaching and training were aimed at GP Ansor Youth, namely female students from the Sirrul Illahiyah Islamic Boarding School Batam to follow all the material that would be presented in this coaching activity, namely the basics of journalism, news writing, and press releases. As a result of this activity, participants gain knowledge and training on journalism, especially in making news and press releases that will be published by the media. The training activities were carried out by the service team for the female students of the Sirrul Illahiyah Islamic Boarding School in the Panaran plot of Tembesi Village for 5 days taking place as planned with 20 children participating. Everyone is enthusiastic and aware of journalism.